The COVID-19 pandemic and changes in the lifestyles of Brazilian adolescents - Deborah Carvalho Malta; Crizian Saar Gomes; Marilisa Berti de Azevedo Barros; Margareth Guimaraes Lima; Alanna Gomes da Silva; Laís Santos de Magalhães Cardoso; André Oliveira Werneck; Danilo Rodrigues Pereira da Silva; Arthur Pate de Souza Ferreira; Dália Elena Romero; Maria Imaculada de Fátima Freitas; Ísis Eloah Machado; et al.
ABSTRACT: Objective: To analyze changes in the lifestyles of Brazilian adolescents during the COVID-19 pandemic. Methods: Cross-sectional study carried out with adolescents who participated in the survey "ConVid Adolescentes - Pesquisa de Comportamentos". The indicators related to lifestyles before and during the COVID-19 pandemic were evaluated: consumption of healthy and unhealthy foods, physical activity and sedentary behavior, smoking and consumption of alcohol. Prevalence and 95% confidence intervals were calculated for the total population and according to sex and age group. Results: A total of 9,470 adolescents participated in the study. During the period of social distancing, there was an increase in the prevalence of vegetables consumption (from 27.34 to 30.5%), frozen foods (from 13.26 to 17.3%), chocolates and sweets (from 48.58 to 52.51%), and time in front of screens (from 44.57 to 70.15%). On the other hand, there was a decrease in the practice of physical activity (from 28.70 to 15.74%) and in the consumption of alcohol (from 17.72 to 12.77%). Differences were observed according to sex and age group. Conclusion: The results show changes in the lifestyle of adolescents and an increase in health risk behaviors.